PENGGUNAAN METODE SNOWBALL THROWING DALAM MENINGKATKAN HASIL BELAJAR IPS KELAS V SDN 007 PURNAMA KECAMATAN DUMAI BARAT KOTA DUMAI - Rosidawati ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The low value of students caused by wrong way teachers teach. Students tend to get bored inthe following subjects in school, because teachers who dominated the peroses learning. Thisresulted in students feel compelled to follow the lessons. This study aims to improve studentlearning outcomes in social studies class V SDN 007 Purnama Kota Dumai. Starting onJanuary 4 until January 12, 2012. The research was conducted on students of class V,totaling 26 people, 15 men, 11 women. This study consisted of two cycles, each cycleconsisting of two meetings. To find out the data of student learning outcomes in learningimplementation using throwing snowball method is to use a written test. As for knowing theactivities of teachers and students are using the observation sheet. The results of thediscussion stated that the activity of students in the first cycle of meeting I just 45.1% lesscategory, while the second meeting of the first cycle of student activity reached 59.2% are stillin the category of less, the first meeting of the second cycle increased to 68.7% still includethe category lacking in cycle II meeting II student activity rose to 86.9 good category. Andlearning outcomes in the first cycle of the first meeting in 1280 with an average of 50 includethe category less, learning outcomes in the first cycle II reached the number of meetings in1850 with an average value of 71.15 include the category enough. In the second cycle ofmeeting the learning outcomes of 2095 amounted to an average of 80.3 including goodcategory. In the second cycle II meeting in 2116 rose an average value of 81.38 bothcategories thus be seen that by throwing a snowball learning model can improve studentlearning outcomes in social studies learning class V SDN 007 Purnama Kota Dumai.